How Objective Are Subjective Measures of Organizational Innovativeness, Really? - Patrycja Klimas (Management and Business Administration. Central Europe, 2014)
Purpose: This paper aims to match subjective and objective measures of organizational innovativeness and test correlative relationship between the two. Methodology: The research adopts a quantitative approach, and applies correlation analysis to identify interdependencies. The study has been done in the aviation industry, as organizational innovativeness has so far been described especially in high-tech industries – however it has not been investigated within aviation industry yet. Findings: The results show that the discussions over reliability of research based on subjective measurements techniques are not unfounded. The evidence suggests that subjective measures are not correlated with objective measures, and the outcomes of third-party investigations differ considerably. Therefore decisions about measurements techniques should be deliberate, thought out, theoretically grounded and justifi ed. In general, methodological recommendations provided by this paper could be boiled down to the ascertainment that accurate and reliable assessment of organizational innovativeness should use a set of objective measures addressing all stages of the innovation process. Originality: It should be noted that this study was restricted to only one industry and prone to some common bias. The aviation industry sample was relatively small and purposefully selected, disallowing conclusive statements made outside of this empirical setting. However despite the limitations this paper provides some significant contribution to evaluation and research on innovativeness. It compares two approaches to measurement and empirically proves which approach is more suitable in case of such a highly innovation-intensive sector like aviation. Moreover, it introduces a new in Polish research tool for subjective assessment of organizational innovativeness namely the questionnaire developed by Wang and Ahmed (2004).